ANALISIS TINDAK TUTUR ILOKUSI PADA PIDATO KENEGARAAN PRESIDEN JOKO WIDODO DALAM SIDANG TAHUNAN MPR 2018-2022 DAN IMPLEMENTASI TERHADAP BAHAN AJAR - Fitraulya Balqis; Any Budiarti; Frilia Shantika Regina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to describe the types, functions and to find out illocutionary speech acts in President Joko Widodo's state address at the 2018-2022 MPR annual session regarding the implementation of teaching materials. Speech is an expression of thoughts in the form of words shown to the audience. The research method used in this research is descriptive qualitative research method. Descriptive qualitative research is research that analyzes data inductively and the results emphasize meaning. This research focuses on analyzing the speech acts conveyed by President Joko Widodo in the 2018-2022 MPR annual session. Speech acts are often said to be actions that are displayed by producing an utterance, illocutionary speech act an utterance that serves to inform something and serves to do something. Speech act is one of the elements of pragmatics involving the speaker, listener or writer, reader and what is being discussed. Speech acts are divided into three types, namely locutionary, illocutionary and perlocutionary speech acts. This study focuses more on illocutionary speech acts, illocutionary speech acts have five different types, namely assertive, directive, expressive, declarative and commissive. The results of the research in President Joko Widodo's State of the Union speech at the 2018-2022 MPR annual session found various types of illocutionary speech acts that differ according to the speech delivered by President Joko Widodo.